Immune Checkpoint Inhibitors and Survival Outcomes in Brain Metastasis: A Time Series-Based Meta-Analysis - Hu, Xingjiang; Yu, Hui; Zheng, Yunliang; Zhang, Qiao; Lin, Meihua; Wang, Jialei; Qiu, Yunqing (Frontiers in Oncology, 2020)
Immune checkpoint inhibitors (ICIs) have shown potential to improve the prognosis of patients with brain metastasis (BM) caused by advanced cancers. However, controversies still exist in regard to its survival benefits. In the present work, a time series-based meta-analysis of phase I/II/III trials and observational studies were performed to evaluate the differences in mortality of ICI-treated BM patients. A number of public library databases, including MEDLINE, EMBASE, OVID, and COCHRANE, were systemically searched by March 2019. The quality of included studies was assessed by the Newcastle-Ottawa Scale (NOS) scoring. Outcome measures here established were mortality and progression-free survival (PFS) at different follow-up endpoints. Survival rates and curve data were pooled for further analysis. To detect the data heterogeneity, subgroup analyses were conducted according to tumor and ICI types. Eighteen studies, 6 trials and 12 controlled cohorts were assessed, involving a total of 1330 ICI-treated BM patients. The 6-month survival rate and PFS were 0.67 (95%CI: 0.59-0.74) and 0.36 (95%CI: 0.24-0.49), respectively. According to the tumor type (melanoma, NSCLC, and RCC), subgroup analyses indicated that melanoma presented the lowest survival rates among the three groups here selected. In regard to the type of ICIs, the combination of CTLA-4 and PD-1/PD-L1 showed the best survival outcome in these groups. The 12-month survival rate and PFS showed a consistent pattern of findings. In the long-term, the 24-month survival rate and PFS were 0.20 (95%CI: 0.12-0.31) and 0.18 (0.05-0.46) in BM patients. Hence, ICI therapy may be associated with an improved prognosis of BM patients. However, current research presented a limited study design. Multicentre randomized trials may later assist in validating ICI-based therapies for a better outcome of BM patients.